Automatização da ventilação em galpão de frango de corte através do Índice Entalpia de Conforto (IEC) - Queiroz, Marília Lessa de Vasconcelos (2018)
The Northeast region of Brazil presents environmental conditions that allow the production of broiler chicken at large scale, however, the fact that high temperatures predominate throughout the year, makes the artificial climatic mechanisms become a primordial tool for thermal comfort of the birds confined in the breeding sheds. On the other hand, it is common to observe that these mechanisms are generally used without criteria, so that inadequate ventilation and excessive nebulization may result in financial loss for farms, since the combination of high temperatures and relative humidity can affect the thermal comfort of birds. Thus, the objective of this work was to evaluate the performance of a Comfort Enthalpy Sensor Prototype (PSEC), in automation of ventilation and aid in the nebulization of a broiler chicken shed, according to the Enthalpy Comfort Index (IEC) and to compare the values of the index in question with the results obtained in an shed without automation in a commercial farm located in Ceará, Brazil. The two sheds, initially containing 22.500 broiler chickens from the Ross lineage, were monitored daily from the 4th week of accommodation, during which period were collected environmental data (temperature and relative humidity and IEC), physiological data (rectal temperature, respiratory rate, and body weight gain) and behavioral data. The collected data from environmental, physiological and behavioral variables were confronted to verify the performance of the shed with and without automation of the air conditioning system, in the morning and afternoon shifts. According to the data of the environmental variables collected by PSEC, in the 4th week the IEC average in the automated shed was between 52.1 and 57.7 kJ/kg of dry air in the morning shift and between 57.8 to 69.9 kg/kg of dry air in the afternoon shift. These averages were lower (p<0.05) than the means of the meteorological data loggers, which indicated IEC values between 69.8 and 80.1 kJ/kg of dry air. Due mainly to the low IEC calculated values, PSEC didn’t indicate the need for ventilation in the 4th week in the automated shed. In the 5th and 6th week, PSEC obtained averages that indicated an alert IEC condition, however, the meteorological<l data loggers showed a critical condition in both sheds that differed statistically (p<0.05) from the means of PSEC. The analysis of the physiological variables showed that, in both sheds, the birds were in a situation of thermal stress. Through Failure Mode and Effect Analysis (FMEA) the most critical parts of PSEC were observed and recommendations were made for corrections to these processes in order to contribute to the improvement of the prototype in question.